Human Resource Management Implementation to Achieve Institutional Vision at Muhammadiyah Boarding School Tangerang - Hadiwijaya, Dudung; Murniadi, Murniadi; Ardiyanti, Anita; Sutarman, Sutarman (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to explore: 1) the implementation of human resource management (HRM) in achieving the institutional vision at Muhammadiyah Boarding School Tangerang for the academic year 2020/2021, 2) the supporting and hindering factors in HRM implementation towards achieving the vision, and 3) solutions applied to address obstacles in HRM implementation to support institutional goals. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation. Data analysis followed Miles and Huberman’s interactive model, which includes data reduction, data presentation, and conclusion drawing or verification. Findings indicate that: 1) HRM implementation at Muhammadiyah Boarding School Tangerang to achieve the institutional vision was carried out in stages, including planning, recruitment, selection and placement, training and development, evaluation, and supervision. 2) Supporting and hindering factors in HRM implementation include coordination challenges in planning during the pandemic, lack of qualified candidates during recruitment, time constraints in training and development, insufficient scheduled evaluation periods, and the absence of continuous oversight due to the lack of a dedicated supervisory team from the school. 3) Solutions to these obstacles involve enhancing coordination between the Director, head of the school, and other relevant authorities in aspects of planning, placement, human resource development, and scheduling synchronization for performance evaluation and supervision.